(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article deals with the use of modern innovative methods in teaching language disciplines at the university. Information competence, which has become one of the main indicators of quality education, is one of the main conditions for modern education, and its formation directly depends on the active work of students in an open educational environment.